Living With Lovebugs - Norman C. Leppla (EDIS)
ENY-840, a 7-page illustrated fact sheet by Norman C. Leppla, describes this seasonally abundant nuisance pests also known as March flies, double-headed bugs, honeymoon flies, united bugs, ... and some expletives that are not repeatable. The author discusses several myths about these much-maligned creatures and describes some of the benefits they provide as well as tips for coping with them. Includes references. Published by the UF Department of Entomology and Nematology, January 2007.